KESADARAN ESENSIAL MOTIVASI BELAJAR AGAMA ISLAM PADA KAUM MUALAF SUKU AKIT DESA PENYENGAT KECAMATAN SUNGAI APIT KABUPATEN SIAK - Santoso, Santoso; Safitri, Ajeng (UIR Press, 2019)
Abstract This study aims to reveal the essential awareness of the motivation to learn Islam, the converts of the Akit tribe. The research location was in Penyengat Village, Sungai Apit District, Siak Regency. Research respondents were converts to the Akit tribe, amounting to 30 people. This study used qualitative method with a phenomenological approach. From the results of this study, it was concluded that; (1) the Akit tribe is essentially a 'religious' society. There are various symbolic cultures that are identical to Islamic values. This shows that in essence culture has become a medium of learning Islam for converts for a long time. Spiritual beliefs about the mysteries possessed by traditional communities generally have relevance to official religious principles, especially Islam.; (2) Based on the limitations of the traditional mindset of society, the use of local symbols is an effective medium of communication in building the direction of transformation of beliefs in traditional communities. The style of communication with local symbols psychologically fosters an attitude of acceptance and a higher sense of belonging to the values ​​of new beliefs. Keywords: essential awareness, learning motivation, converts to akit tribes   Abstrak Penelitian ini bertujuan untuk mengungkap kesadaran esensial dari motivasi untuk belajar Islam, mualaf dari suku Akit. Lokasi penelitian di Desa Penyengat, Kecamatan Sungai Apit, Kabupaten Siak. Responden penelitian adalah kaum mualaf suku Akit, berjumlah 30 orang. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologis. Dari hasil penelitian ini, disimpulkan bahwa; (1) suku Akit pada dasarnya adalah masyarakat 'religius'. Terdapat berbagai simbol budaya yang identik dengan nilai-nilai religiusitas Islam pada masyarakat suku Akit. Ini menunjukkan bahwa pada dasarnya budaya telah menjadi media pembelajaran Islam bagi kaum mualaf suku Akit sejak lama; (2) keterbatasan pola pikir masyarakat suku Akit, memerlukan media simbol-simbol lokal sebagai alat komunikasi dalam membangun arah transformasi kepercayaan pada masyarakat tradisional suku Akit. Gaya komunikasi dengan simbol-simbol lokal secara psikologis menumbuhkan sikap penerimaan dan rasa memiliki yang lebih tinggi terhadap nilai-nilai keyakinan baru. Kata kunci: kesadaran esensial, motivasi belajar, mualaf suku akit